2013
DOI: 10.1038/srep01141
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling LOX-1 receptor interplay with nanotopography: mechanotransduction and atherosclerosis onset

Abstract: Lectin-like ox-LDL receptors (LOX-1) play a crucial role in the ox-LDL–induced pathological transformation of vessel-wall components, a crucial early step in atherogenesis. LOX-1 dynamics is quantitatively investigated in human endothelial cells (HUVECs) exposed to environmental nanotopographies. We demonstrate distinct nanotopography-induced cell phenotypes, characterized by different morphology, LOX-1 diffusivity and oligomerization state: HUVECs on flat surfaces exhibit the behavior found in pro-atherogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…While COC biocompatibility was already reported3839, nanopatterning by itself could in principle influence cell viability40 by altering cell morphological and functional properties. Experiments were performed at short and medium term: 24 hours and 1 week after seeding.…”
Section: Resultsmentioning
confidence: 99%
“…While COC biocompatibility was already reported3839, nanopatterning by itself could in principle influence cell viability40 by altering cell morphological and functional properties. Experiments were performed at short and medium term: 24 hours and 1 week after seeding.…”
Section: Resultsmentioning
confidence: 99%
“…Mimicking the topographically and biochemically complex environment of the extracellular matrix (ECM) on synthetic substrates such as PVA may help direct specific biological actions such as improving cell adhesion and decreasing platelet activation. For example, mimicking the fibrillar ECM structure in the form of micron-sized gratings on synthetic surfaces has been shown to increase migration and retention under shear stress [15], improve proliferation [16] and retain the atheroprotective phenotype [17] of endothelial cells. Additionally, functionalization of synthetic surfaces with ECM proteins, such as fibronectin [18], vitronectin [19] and laminin [20] were shown to improve endothelial cell attachment.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was shown that by performing FCS on differently-sized observation areas one can define an “FCS diffusion law” enlightening hidden features of molecular motion 11,12 . Besides being varied in size, the focal area was also duplicated 13 , moved in space along lines 1420 or conjugated with fast cameras 21,22 . Using these ‘spatio-temporal’ correlation approaches, relevant biological parameters of several membrane components were quantitatively described on both model membranes and actual biological ones, thus yielding insight into membrane spatial organization.…”
Section: Introductionmentioning
confidence: 99%